2014
DOI: 10.1155/2014/575181
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Papillary and Clear Renal Cell Carcinoma in the Same Kidney

Abstract: Renal cell carcinoma (RCC) is the most common solid lesion of the kidney. Bilateral synchronous benign and malignant renal tumors have been defined in some reports. However, unilateral concordance of malignant renal tumors is very rare and there are only a few cases that had synchronous different subtypes of malignant renal tumors arising within the same kidney. Herein, we describe a 67-year-old male patient who had clear cell RCC and papillary RCC in his right kidney that were successfully treated with radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Previously have been reported cases where distinct combination of subtypes of renal cell carcinoma (clear cell, papillary, chromophobe, collecting duct) occurs synchronously in the same kidney. 1 , 2 , 3 , 4 , 5 According with Ustuner M. et al (2014), 3 the association of a papillary renal cell carcinoma and a clear cell renal cell carcinoma only have been reported in another two cases, thus correlating with our case. Remarkably, due to unknown causes, the left kidney is affected mostly as in this case report.…”
Section: Discussionsupporting
confidence: 86%
“…Previously have been reported cases where distinct combination of subtypes of renal cell carcinoma (clear cell, papillary, chromophobe, collecting duct) occurs synchronously in the same kidney. 1 , 2 , 3 , 4 , 5 According with Ustuner M. et al (2014), 3 the association of a papillary renal cell carcinoma and a clear cell renal cell carcinoma only have been reported in another two cases, thus correlating with our case. Remarkably, due to unknown causes, the left kidney is affected mostly as in this case report.…”
Section: Discussionsupporting
confidence: 86%
“…Adults, compared to children, are more susceptible to KIRC, and immune-related genes (IRGs) play a vital role in the development of this type of cancer [ 19 ]. However, both KIRC and KIRP may coexist in the same kidney [ 22 ]. Many reports showed that SARS-CoV-2 might cause direct kidney injury due to the high expression of ACE2 in the renal tissue, and multiple factors such as endothelial cell injury, host immune clearance, and immune tolerance disorders, and lipid metabolic disorders, etc.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Simhan et al 19 reported a data of 97 patients who had multifocal renal tumors. They reported 8 patients who had mixed papillary and clear cell RCC, all of which were treated with partial nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…3 cases in this study had synchronous papillary and clear cell RCC and were treated by radical nephrectomy. Ustuner et al 21 reported a case of 67 year old male who had clear cell and papillary RCC in right kidney, that were successfully treated with radical nephrectomy.…”
Section: Discussionmentioning
confidence: 99%